Analisis Kapabilitas Proses Mesin Tenon dan Mortise Produk Bangku Kebun - Mohammad, Gunawan; Sulistyawati, Dwi Retna; Kausar, Alfin (Metode : Jurnal Teknik Industri, 2024)
This research focuses on the process of producing pins and holes from tenon and mortise machines. Every time the production process, namely 20 sets, experiences a failure of 20%, the characteristics of the failure are a large size between the size of the purus and the wrong hole which does not match the specifications expected by consumers. The company has a target length of the purus and depth of the hole of 30 mm as well as the width of the purus and the width of the hole. 60 mm with a tolerance limit of 2 mm. This research aims to control the process capabilities of tenon and mortise machines. The method used in this research is the IMR control chart to determine the machine process capability value (Cp) and the process capability index value (Cpk). The results of the research show that in the calculation of process capability in the dimensions of shaft length, shaft width, depth of hole and hole, all four do not meet specifications. After analyzing the process capability, the cause of the defect is then searched for using a fishbone diagram, namely creating improvement proposals using the Poka Yoke method. Results of the fishbone diagram: human factors are the dominant factor causing defects. To minimize defects due to human factors, it is necessary to design an ultrasonic distance sensor as a warning function for operators using the Poka Yoke method. The results of applying an ultrasonic distance sensor can increase the process capability value to be in accordance with specifications.